Advances in Multimedia Information Processing - PCM 2010 11th Pacific Rim Conference on Multimedia, Shanghai, China, September 21-24, 2010, Proceedings, Part I - Qiu, Guoping; Lam, Kin Man.; Kiya, Hitoshi; Xue, Xiang-Yang.; Kuo, C.-C. Jay.; Lew, Michael S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 11th Pacific Rim Conference on Advances in Multimedia Information Processing, held in Shanghai in September 2010.
Multimedia Analysis and Retrieval -- Composition Based Semantic Scene Retrieval for Ancient Murals -- Feature-Preserving 3D Thumbnail Creation via Mesh Decomposition and Approximation -- Correlation-Based Feature Selection and Regression -- A Simple Content-Based Strategy for Estimating the Geographical Location of a Webcam -- Improving Video Concept Detection Using Spatio-Temporal Correlation -- Novel Spectral Descriptor for Object Shape -- A Multi-layer Scene Model for Video Surveillance Applications -- Practical Implementation of Super-Resolution Approach for SD-to-HD Video Up-Conversion -- Image Histogram Constrained SIFT Matching -- A Method for Music Structure Analysis Using MPEG-4 TwinVQ Audio Compression -- A Blind Reference-Free Blockiness Measure -- Learning Contextual Metrics for Automatic Image Annotation -- Real Time Tunnel Based Video Summarization Using Direct Shift Collision Detection -- Boosting Multimodal Semantic Understanding by Local Similarity Adaptation and Global Correlation Propagation -- A New Image Quality Assessment Model Based on the MPEG-7 Descriptor -- A Complete Visual Hull Representation Using Bounding Edges -- Discovering Phrase-Level Lexicon for Image Annotation -- Action Recognition Based on Learnt Motion Semantic Vocabulary -- Video Summarization with Visual and Semantic Features -- Scene Categorization Using Boosted Back-Propagation Neural Networks -- People Detection by Boosting Features in Nonlinear Subspace -- Multilinear Tensor Supervised Neighborhood Embedding Analysis for View-Based Object Recognition -- Color Spectrum Normalization: Saliency Detection Based on Energy Re-allocation -- An Experience Oriented Video Digesting Method Using Heart Activity and Its Applicable Video Types -- Abnormal Change Detection of Image Quality Metric Series Using Diffusion Process and Stopping Time Theory -- A Video Text Detection Method Based on Key Text Points -- Commercial Recognition in TV Streams Using Coarse-to-Fine Matching Strategy -- Automatic Video Abstraction via the Progress of Story -- Efficient Foreground Layer Extraction in Video -- Robust Shape Retrieval through a Novel Statistical Descriptor -- A New Text Detection Algorithm for Content-Oriented Line Drawing Image Retrieval -- 3D Similarity Search Using a Weighted Structural Histogram Representation -- A Hybrid Moving Object Detection Method for Aerial Images -- A Vehicle Color Classification Method for Video Surveillance System Concerning Model-Based Background Subtraction -- Efficient Temporal Segmentation for Sports Programs with Special Cases -- An Effective Video Text Tracking Algorithm Based on SIFT Feature and Geometric Constraint -- A Novel Metrics Based on Information Bottleneck Principle for Face Retrieval -- On Vocabulary Size in Bag-of-Visual-Words Representation -- A Determined Binary Level Set Method Based on Mean Shift for Contour Tracking -- Adaptive Particle Filter Based on Energy Field for Robust Object Tracking in Complex Scenes -- 3D Model Retrieval Using 2D View and Transform-Based Features -- An Approach to the Compact and Efficient Visual Codebook Based on SIFT Descriptor -- Adaptive Energy Diffusion for Blind Inverse Halftoning -- Structuring Sport Video through Audio Event Classification -- A New Shape Descriptor for Object Recognition and Retrieval -- Training Strategy of Semantic Concept Detectors Using Support Vector Machine in Naked Image Classification -- Unifying Content and Context Similarities of the Textual and Visual Information in an Image Clustering Framework -- Depth Estimation of Face Images Based on the Constrained ICA Model -- Personalized Content Adaptation Using Multimodal Highlights of Soccer Video -- SAR Image Segmentation Based on Kullback-Leibler Distance of Edgeworth -- A Fast Video Copy Detection Approach by Dynamic Programming -- Two-Stage Localization for Image Labeling -- Multimedia Security and Right Management -- Duplication Localization and Segmentation -- Identifying Steganographic Payload Location in Binary Image -- Cryptanalysis of an Image Encryption Scheme Using Cellular Automata Substitution and SCAN -- Improved DE-Based Reversible Watermarking Using Sorting and Histogram Shifting -- Privacy-Preserving Watch List Screening in Video Surveillance System -- Hybrid SVD-Based Audio Watermarking Scheme -- A Novel Multi-size Block Benford$1 (Bs Law Scheme for Printer Identification -- A Reversible Data Hiding Scheme for JPEG Images -- Affine Resilient Image Watermarking Based on Trace Transform -- Histogram-Based Reversible Data Hiding -- Statistical Analysis of Image Quality Metrics for Watermark Transparency Assessment -- Scalable and Credible Video Watermarking towards Scalable Video Coding -- Protecting Biometric Templates Using Authentication Watermarking -- Non-blind Image Deconvolution with Adaptive Regularization -- Robust Lip Segmentation Method Based on Level Set Model.s
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Multimedia systems; Computer Science; Multimedia Information Systems; Computer Communication Networks; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; User Interfaces and Human Computer Interaction; Software Engineering